Analisis Kinerja Keuangan Perusahaan Dagang PT. Ace Hardware Indonesia, Tbk Di Bursa Efek Indonesia Periode 2014 - 2019 - Abd Halim; Indria Mayesti; Rika Neldawaty; Sri Wahyuni (Universitas Batanghari Jambi, 2020)
The purpose of this study is to explain the Analysis of Corporate Financial Performance (Case Study PT. ACE HARDWARE Indonesia, Tbk). This study aims to determine how the financial performance of the company PT. As seen from the Liquidity ratio of Ace Hardware Indonesia in the Indonesia Stock Exchange in the 2014-2019 period? 2) How is the financial performance of PT. Seeing the solvency ratio for Ace Hardware Indonesia on the Indonesia Stock Exchange in the 2014-2019 period? 3) How is the financial performance of PT. Ace Hardware Indonesia on the Indonesia Stock Exchange seen in the Rentability Ratio in the 2014-2019 period? The results of the study are based on the results of the liquidity ratio consisting of the current ratio and the quick ratio as a whole in the company PT. Ace Hardware Indonesia for the 2014-2019 period shows a liquid company condition where liquidity is used maximally by the company to generate revenue. Solvency ratios consist of Debt to Asset Ratio and Debt to Equity as a whole in the company PT. Ace Hardware Indonesia shows a solvable company condition. Keywords: Performance, Rentability, Solvency and Profitability